Delay of gratification: a comparison study of children with Down syndrome, moderate intellectual disability and typical development. Issue 9 (4th March 2016) - Cuskelly, M.; Gilmore, L.; Glenn, S.; Jobling, A.
Abstract: Background: Self‐regulation has been found to be an important contributor to a range of outcomes, with delay of gratification (a self‐regulatory skill) predicting better academic, social and personal functioning. There is some evidence that individuals with Down syndrome have difficulty with delay of gratification. We investigated the question of whether this difficulty is common to intellectual disability irrespective of aetiology, or whether it presents a particular problem for those with Down syndrome. The latter was considered a possibility because of language difficulties in this group. Method: Three groups of children with a mean MA between 36 and 60 months participated in the study: children with Down syndrome ( n = 32), children with a moderate intellectual disability from a cause other than Down syndrome ( n = 26) and typically developing children ( n = 50). Children completed a series of measures of language and cognitive functioning and participated in a delay of gratification task. Results: The group of children with Down syndrome delayed for a significantly shorter time than either of the other two groups that did not differ from each other. Receptive language was associated with delay time for the children with Down syndrome but not for the typically developing group, nor for the group with moderate intellectual disability. Conclusions: Children with Down syndrome appear to have a particular difficulty with delay of gratification. Language abilities would seem to be implicated in this difficulty, although further examination of this hypothesis is required.